Effectiveness of Entomopathogenic Hyphomycetes Towards Controlling the Broad Mite, Polyphagotarsonemus Latus (Banks) and the Red Spider Mite, Tetranychus Urticae Koch Complex - Nugroho, Ihsan (2003)
he red spider mite, Tetranychus urticae Koch Complex and the broad mite, Polyphagotarsonemus latus (Banks) are serious pests on many agricultural and ornamental crops. They are distributed worldwide and polyphagous on vegetables especially those under shelter and fruit crops. In Malaysia strawberries are usually damaged by the red spider mite while the broad mite is a serious pest on chilli. Chemical insecticides have been the mainstay for controlling these mites. In recent year, the use of microbial control agent such as Bacillus thuringiensis has become increasingly attractive as a biocontrol agent and has become important as one of the biological control components in I PM programmes. In this respect, the potential of entomopathogenic fungi including Beauveria bassiana (8als.) Vuill. , Metarhizium anisopliae (Metch) Sorokin and Paecilomyces fumosoroseus (Wise) 8rown Smith were investigated as microbial control agents against the red spider mite T. urticae and the broad mite P. latus in the laboratory. Field efficacies of selected isolates i n wettable powder formulations were also assessed against the broad mite on chilli. Pathogenicity tests indicated that the above mentioned three isolates were able to cause significant mortalities on the larvae, nymph and adult red spider mite T. urticae and broad mite P. latus. Paecilomyces fumosoroseus (PfPp) was the most pathogenic against the red spider mite followed by M. anisopliae (MaPs) and B. bassiana (BbGc), while B. bassiana (8bGc) was the most infective against broad mite followed by P. fumosoroseus (PfPp) and M. anisopliae (MaPs).